THE PROBLEM OF THE BREST UNION IN HISTORICAL LITERATURE OF XIX AND XX CENTURIES (Pedagogy of Higher and Secondary Education, 2002)
The article shows the role of the Brest union in the formation of national consciousness o f the Ukrainian nobility and Cossacks.